The performance of Miscanthus hybrids in saline-alkaline soil - Zheng, Cheng; Yi, Zili; Xiao, Liang; Sun, Guorong; Li, Meng; Xue, Shuai; Peng, Xiaoying; Duan, Meijuan; Chen, Zhiyong (Frontiers in Plant Science, 2022)
Cultivating the dedicated biomass crop Miscanthus on marginal land is a sustainable means of avoiding competition with food crops for arable land. A large proportion of global marginal land is saline–alkaline; however, little is known about the performance of Miscanthus in saline-alkaline soil. In this study, Miscanthus giganteus and ten other Miscanthus hybrids grown in the Yellow River Delta were exposed to low and saline–alkaline soils during the 2016–2018 growing season to evaluate the agronomic traits, biomass quality and the potential productive index of eleven Miscanthus genotypes. Plant biomass, plant height, and tiller number significantly decreased in high saline–alkaline soil. In particular, the average plant biomass of ten Miscanthus hybrids in low saline–alkaline soil in 2017 and 2018 were 0.21 and 2.25 kg per plant, respectively, and in high saline-alkaline soil were 0.13 and 0.65 kg per plant, respectively. Cell wall, cellulose, and nitrogen content of all genotypes significantly decreased in high saline–alkaline soil, while hemicellulose, ash, sodium, potassium, magnesium, and calcium content significantly increased. However, high saline–alkaline soil had no observable impact on lignin content of Miscanthus biomass. The potential productive indexes of A5, Y11, Y14, Y20, and Y39 were higher than that of Miscanthus×giganteus under low and high saline-alkaline soils. The effect of high saline-alkaline on biomass quality parameters could provide important information for the application of Miscanthus biomass in saline-alkaline soil. The selected genotypes could be considered as breeding materials in saline-alkaline soil.